Superhydrophobic graphene-coated sponge with microcavities for high efficiency oil-in-water emulsion separation. Issue 34 (24th August 2020) - Han, Longxiang; Bi, Hengchang; Xie, Xiao; Su, Shi; Mao, Peng; Sun, Litao
Abstract : We present a graphene-coated sponge for high flux and high efficiency oil-in-water emulsion separation through superhydrophobic microcavities. Abstract : Materials for emulsion separation with low pressure, high flux and high stability are of great interest in the treatment of oily wastewater. Herein, we report a facile strategy for the fabrication of PDMS and graphene coated melamine sponge (PG-MS), which can efficiently separate oil-in-water emulsions. In PG-MS, melamine sponge (MS) provides a three-dimensional porous structure, graphene constructs hydrophobic microcavities, and PDMS enhances the hydrophobic property of the material, forming a superhydrophobic material. The PG-MS shows high flux (experimentally 10 000 L m −2 h −1, and the effective flux increases with the thickness of the filter layer), high separation efficiency (oil content of the filtered water ∼4.7 mg L −1 can be discharged directly, with oil separation efficiency >99%), low pressure (applied to overcome water's gravity), and high stability (no obvious change in 20 cycles). Our study indicates that PG-MS has a wide range of applications in oil-in-water emulsion separation in industry and environmental sciences.